UPAYA UNI EROPA (UE) DALAM MENANGANI KRISIS PENGUNGSI DI KAWASAN UNI EROPA - Lalu Puttrawandi Karjaya (Journal of Innovation Research and Knowledge, 2022)
The refugee crisis that has occurred in the EU region since 2015 has left the EU overwhelmed and has to seek ways to overcome the crisis as the crisis inevitably pose a threat to both the EU and the refugees. This paper describes the various attempts by the EU to address these issues with the challenges it faces. Using the concept of "refugees" and "Dublin regulation" to aid the exposure. While the methodology is used a qualitative methodology by focusing on the narrative (descriptive) to describe the various efforts. This paper concludes that the EU's efforts to address the refugee crisis are in three ways: organizing the agenda through the European Agenda on Migration, then proceeding to make some changes or reform the Dublin or Dublin Regulation / Dublin System Regulation, and made an agreement with Turkey called the European Union (EU) -Turkey Agreement. These efforts ultimately begin to show a small success as the reduction of the coming of refugees, yet there are always other challenges that the EU must face behind it